1987
DOI: 10.1093/oxfordjournals.aje.a114684
|View full text |Cite
|
Sign up to set email alerts
|

Snow Mountain Agent Gastroenteritis From Clams

Abstract: A 1983 investigation of two clambake-related gastroenteritis outbreaks in Rochester, New York, showed that 84 (43%) of 196 persons interviewed had an acute illness characterized by watery diarrhea, vomiting, and abdominal cramps. None of the ill persons were hospitalized or had complications. Illness was associated with eating raw (p = 0.002) or baked (p less than 0.01) hard-shell clams, with the risk of illness increasing with the total number of clams consumed (p less than 0.01). The median incubation period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…In contrast, an outbreak of food-borne Snow Mountain virus in a nursing home was accompanied by the sudden onset of illness among 41 residents within 48 h of an implicated meal, with subsequent person-to-person transmission to over 100 other residents and staff (37). In another study, a similar epidemiologic appearance was reported for sequential outbreaks of astrovirus type 1-and rotavirus-caused gastroenteritis among geriatric residents of a large psychiatric hospital in which transmission by food was not implicated but could not be thoroughly assessed (81 (47,49,98,110). Oysters, clams, and other shellfish filter virus particles from contaminated water and accumulate them in their tissues.…”
Section: Methods For Norwalk-like Virusesmentioning
confidence: 54%
See 3 more Smart Citations
“…In contrast, an outbreak of food-borne Snow Mountain virus in a nursing home was accompanied by the sudden onset of illness among 41 residents within 48 h of an implicated meal, with subsequent person-to-person transmission to over 100 other residents and staff (37). In another study, a similar epidemiologic appearance was reported for sequential outbreaks of astrovirus type 1-and rotavirus-caused gastroenteritis among geriatric residents of a large psychiatric hospital in which transmission by food was not implicated but could not be thoroughly assessed (81 (47,49,98,110). Oysters, clams, and other shellfish filter virus particles from contaminated water and accumulate them in their tissues.…”
Section: Methods For Norwalk-like Virusesmentioning
confidence: 54%
“…Serologic rises in antibody titer to Norwalk-like viruses have been demonstrated by IEM, RIA, and EIA (8,36,37,46,93,110). An immunoblot assay has recently been developed for one Norwalk-like virus (SRSV-9) in Japan (52).…”
Section: Methods For Norwalk-like Virusesmentioning
confidence: 98%
See 2 more Smart Citations
“…The Norwalk agent has been established through the use of these assays as an important cause of gastroenteritis throughout the world, and serologic surveys have shown a high prevalence of Norwalk antibody in both developed and developing countries (9). More limited studies with SMA have associated this agent with outbreaks of gastroenteritis in various areas of the continental United States (10)(11)(12) and have shown that >50% of adults who have been tested have serum antibody to this virus (7).…”
mentioning
confidence: 99%